Pengaruh Modal Kerja terhadap Profitabilitas pada Perbankan di Negara Kawasan Asia Tenggara - Resa Seftiandini; Isni Andriana; Kemas M. Husni Thamrin (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to determine the effect of working capital on profitability in banking Southeast Asian countries. The type of data used is secondary data. Data collection techniques in this research used documentation studies and literature studies. The data obtained from the documentation study is a dataset from Moody's Analytics BankFocus and documents. All financial data used in this research is expressed in USD units. The population in this study are six countries operating in Southeast Asian countries in 2017-2022 totaling 295 banks using a purposive sampling technique. The sample used was 63 banks in the Philippines, Indonesia, Malaysia, Singapore, Thailand and Vietnam. The data analysis technique used is multiple linear regression analysis using SPSS version 2.6 software. The results showed that the debtor collection period (DCP) had no effect, the creditor payment period (CPP) had a significant positive effect, the cash conversion cycle (CCC) had no effect, and the banking ratio (BR) had a significant positive effect on net profit margin.